2014
DOI: 10.3233/jvr-140716
|View full text |Cite
|
Sign up to set email alerts
|

Employer-recommended strategies to increase opportunities for people with disabilities

Abstract: BACKGROUND: The employment rate among persons with disabilities is less than half the rate among persons without disabilities. Broad innovations are needed to reduce this disparity. OBJECTIVE: We examined employers' perspective related to: a) challenges they face when hiring people with disabilities, b) advantages (i.e. the business case) to employing people with disabilities, and c) their recommendations for innovations in both the public disability employment services systems and their own hiring practices t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 11 publications
0
48
0
Order By: Relevance
“…Frontline employment professionals typically come to the field with limited experience providing job placement for job seekers with disabilities, and even more frequently, with a limited understanding of how to implement effective employer engagement strategies. Nevertheless, they are the primary point of contact in most employer interactions and must be prepared to present a business case for hiring people with disabilities that will be relevant to business necessity (Henry, et al, 2014). During the action planning sessions, many frontline staff expressed the value of having a readily-accessible, relevant, online intervention like Diversity Partners available to provide them with critical knowledge, tips and strategies for employer engagement.…”
Section: Active Engagement With Employment Service Professionalsmentioning
confidence: 99%
“…Frontline employment professionals typically come to the field with limited experience providing job placement for job seekers with disabilities, and even more frequently, with a limited understanding of how to implement effective employer engagement strategies. Nevertheless, they are the primary point of contact in most employer interactions and must be prepared to present a business case for hiring people with disabilities that will be relevant to business necessity (Henry, et al, 2014). During the action planning sessions, many frontline staff expressed the value of having a readily-accessible, relevant, online intervention like Diversity Partners available to provide them with critical knowledge, tips and strategies for employer engagement.…”
Section: Active Engagement With Employment Service Professionalsmentioning
confidence: 99%
“…The main cause identified is the employers' attitude towards hiring disabled person. Employers have a negative perception towards person with disabilities whereby they are concerned that person with disabilities could not perform the task (19)(20)(21)(22). Past literature shows that attitude of managers impact the hiring of PWDs (23)(24)(25) found that attitude influences intention, while in turn, intention predicts behaviour.…”
Section: Employers' Attitudementioning
confidence: 99%
“…A minority of employers are positive about employing people with disability, viewing them as productive and reliable employees . Hiring people with disability can enhance an employer's social reputation (Henry et al 2014), but most employers maintain negative attitudes (Pruett et al 2008) and concerns (Fraser et al 2010) that prevent them from hiring disabled people.…”
Section: Attitudinal Barriers To Employment Opportunities For People mentioning
confidence: 99%
“…Attitudes are reflected in behaviours such as avoidance (Altman 1981). Government efforts to break down barriers to employment for people with disability in Australia have followed international recommendations such as making employment of people with disability easier for employers, incentivising hiring, and providing access to training for employers, their workforce, and people with disability (Henry et al 2014). Differences in work impairments -in disability type and severity -increase the complexity of overcoming employer resistance to hiring people with disability (Tuckerman et al 2012;Waghorn & Hielscher 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation